Integrating HRD with Organization Strategy as a Precursor to Strategic Management: A Review - Sthapit, Arhan (Administration and Management Review, 2011)
To cater to the ever-increasing need for strategically steering the organisation’s managerial practices into strategic management, the most effective way is to integrate the HRD policy and practices with organisational strategy while aligning them with global-arching human resource management. Organisations in both public and private sectors require a critical group of positive factors concerning effective management of human resources to successfully execute their organization strategies and goals. It involves the analysis of a myriad of internal and external environmental factors contingent to the organisation, followed by a strategic approach to influencing key stakeholders and the formulation of strategic HRD policies and plans in parallel with the organisation’s business strategy. Drawing f rom the few key research works available, this article explores the need for integrating the HRD policy and practices with the organisational strategy and assesses the process of integration, so that it warrantees that the organization effectively exercise Strategic Management. Having discussed implications of HRD-Organization strategy integration practices, the article concludes that the organisations should make their HRD function more strategic in nature. Key words: Human Resource Development (HRD); Strategic Management (SM); Strategic Human Resource Management (SHRM); Strategic Human Resource Development (SHRD); Business Environmental Factors (BEFs) Article type: Conceptual/Review Paper Administration and Management Review Volume 22, No. 1, January, 2010 Page: 1-27 Uploaded Date: 2 December, 2011